MEMPERKUAT KESADARAN BERBANGSA DAN BERNEGARA MELALUI PENDIDIKAN KEWARGANEGARAAN DI ERA DIGITAL - Ilham, Annisa Puteri; Triwardani, Dinda Mustika; Adilla, Putri; Hudi, Ilham (Jurnal Teknologi Pendidikan, 2024)
Citizenship education is an important subject that shapes character and increases students' understanding of the country and citizenship. The aim of this subject is to foster a sense of love for the homeland, increase national and state awareness and develop students' abilities so they can participate actively in social life. In an increasingly advanced digital era, the use of technology in citizenship education can be an effective way to increase students' knowledge of citizenship. The use of technology in civic education learning activities can facilitate and make the material more interesting for students, as well as increase student participation in the learning process. This is in line with the challenges of the times in an increasingly advanced digital era, where the integration of technology not only enriches teaching methods, but also allows for a learning experience that is more interactive and connected to existing social realities.